PENGARUH DIFERENSIASI PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN ESSENTIEEL COFFEE SHOP DI BANDUNG - Lestari, Desi; Bernika, Cindy (Transpublika Publisher, 2022)
This study aims to analyze the influence of product differentiation and brand image on consumer satisfaction at Essentieel Coffee Bandung. The method used in this study is a quantitative descriptive method. The population referred to in this study is the number of Essentieel customers over the past 1 month. From the results of the discussion about the influence of product differentiation and brand image on consumer satisfaction at Essentieel Coffee Bandung. So the final conclusion of this study is as follows: Product Differentiation and brand image have a significant effect on consumer satisfaction at Essentieel Coffee Bandung. This is based on the results obtained. This research is still limited to the creation of perceptions based on the marketing theory of Product Differentiation applied by new business people. Then the researcher processes the data from the results of the study and obtains conclusions that can basically be realized or become consideration for the improvement of a new business. Furthermore, researchers can develop and deepen this research in order to obtain other impacts, for example by examining Product Differentiation from the service and product side together so as to give rise to the possibility of new influences between the variables studied.